Effect of surface modification on the interfacial tension between the melts of high-density polyethylene and Nylon 66: Correlation between rheology and morphology - Kim, HJ; Seo, Y (AMER CHEMICAL SOC, 2003)
This paper presents the effect of a low-energy Ar+ ion-beam irradiation on the interfacial tension between high-density polyethylene (HDPE) and Nylon 66 (Ny66). Ny66 was melt blended in a twin screw extruder with two different kinds of HDPE (pristine HDPE and HDPE with its surface modified by low-energy ion-beam irradiation (IBHDPE)). The viscoelastic dynamic moduli of two kinds of HDPE/Ny66 blends in the molten state have been measured in a cone and plate rheometer as a function of the frequency. The rheology of the blends was fit to three theoretical models (the Palierne model, the Choi-Schowalter (CS) model, and the Lee-Park (LP) model) to infer the values of the equilibrium interfacial tension. For pristine HDPE/Ny66 blends, all three models predict the linear viscoelastic data pretty well despite the relatively high concentration of the dispersed phase. The values of the interfacial tension calculated for the IBHDPE/Ny66 blends were less than those of the unmodified HDPE/Ny66 blends, which indicates the effect of surface functionalization. For IBHDPE/Ny66 blends, predictions of the Palierne and the CS models show some discrepancies from the experimental data in the low-frequency region. The LP model provides a better prediction in the low-frequency region but it shows deviations in the high-frequency region. A modified LP model gives a better description of changes in the interfacial tension with irradiation time. Explanations for the model predictions and modifications of the theoretical models are provided.
Keywords: IMMISCIBLE POLYMER BLENDS; LINEAR VISCOELASTIC BEHAVIOR; DYNAMICS